Mulammaâ (Macaronic) Verse: The Link between Persian and Arabic poetry - Ali Asghar Ghahramani Moqbel (دراسات فی اللغه العربیه و آدابها, 2011)
Â Â  âMacaronicâ literally refers to an attribute for a thing which possesses two colors or two dissimilar qualities, and âmacaronic verseâ, in Arabic rhetoric, points to a kind of poem whose words in one hemstitch or in the whole stitch are composed of words which include dotted letters (moâjamah) whereas the words in another hemstitch or stitch possess letters with no dots (mohmalah). Macaronic verse in the contemporary Arabic poetry, however, refers to a kind of poem in which the first hemstitches are formal in diction while the second ones are totally informal and/or colloquial. Nonetheless, what interests us here in this article is the use of macaronic verse in Persian poetry. It refers to a kind of poem which is composed of two different languages (generally Persian and Arabic). Â  The main question for which we seek to find an answer in this paper is: How can one compose a poem in two languages while niether deviates from each languageâs (Arabic or Persian) specific linguistic and metrical norms? We have found the answer to the question in the kind of the meter, in their metrical system that is, meter in both Arabic and Persian poetry is based on the quantity of the syllables. In other words, the basis of their rhythm is quantitative. This is the main principle that eases the task of composition for the poet. However, there are subtle differences in the metrical systems of the two languages such as the length of the hemstitches and cases of poetic licenses. Meanwhile, since the macaronic verse was innovated by the Iranians, it follows the principles of Persian poetry concerning the nuances as well as the minute features of meter. That is why most of the poetry written in this fashion has assumed Persian poetryâs tone and spirit. Because the subject we have chosen to discuss demands comparison between the two kinds of poetry written in Persian and Arabic languages, our research approach is eventually comparative